Learning to Classify Organic and Conventional Wheat – A Machine Learning Driven Approach Using the MeltDB 2.0 Metabolomics Analysis Platform - Kessler, Nikolas; Bonte, Anja; Albaum, Stefan P.; Mäder, Paul; Messmer, Monika; Goesmann, Alexander; Niehaus, Karsten; Langenkämper, Georg; Nattkemper, Tim W. (Frontiers in Bioengineering and Biotechnology, 2015)
We present results of our machine learning approach to the problem of classifying GC-MS data originating from wheat grains of different farming systems. The aim is to investigate the potential of learning algorithms to classify GC-MS data to be either from conventionally grown or from organically grown samples and considering different cultivars. The motivation of our work is rather obvious on the background of nowadays increased demand for organic food in post-industrialized societies and the necessity to prove organic food authenticity. The background of our data set is given by up to eleven wheat cultivars that have been cultivated in both farming systems, organic and conventional, throughout three years. More than 300 GC-MS measurements were recorded and subsequently processed and analyzed in the MeltDB 2.0 metabolomics analysis platform, being briefly outlined in this paper. We further describe how unsupervised (t-SNE, PCA) and supervised (RF, SVM) methods can be applied for sample visualization and classification. Our results clearly show that years have most and wheat cultivars have second-most influence on the metabolic composition of a sample. We can also show, that for a given year and cultivar, organic and conventional cultivation can be distinguished by machine-learning algorithms.